If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7X + -3(7X + 12) = 104 Reorder the terms: -7X + -3(12 + 7X) = 104 -7X + (12 * -3 + 7X * -3) = 104 -7X + (-36 + -21X) = 104 Reorder the terms: -36 + -7X + -21X = 104 Combine like terms: -7X + -21X = -28X -36 + -28X = 104 Solving -36 + -28X = 104 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '36' to each side of the equation. -36 + 36 + -28X = 104 + 36 Combine like terms: -36 + 36 = 0 0 + -28X = 104 + 36 -28X = 104 + 36 Combine like terms: 104 + 36 = 140 -28X = 140 Divide each side by '-28'. X = -5 Simplifying X = -5
| 5x-10=-6x+111 | | 8c-22=-60 | | -.4x^2+28x-200=0 | | 5+1-3= | | -6x+6=4x+6 | | -6m=-2n-4n | | 4n-10-3+n= | | 3.5x=161 | | x^2+y^2-6x+18y+74=0 | | 7x+1=22+4x | | 3=1.5n | | 4x+7-8x+10= | | 7x-10=3x+30 | | 550=45+315 | | 7x-2=4x+13 | | 49=k^2 | | 6-10x+8x=-34 | | 10-7x=-4x+7 | | -5x-6x=22 | | 18x+9=9x+47 | | 4-3x=4x-45 | | (4-8)= | | -7(9-6x)=287 | | 4+2x=-2x-8(5x+5) | | -3(8)+4=y | | 2x-3+103=180 | | .25(12x-8)=7 | | -24=7+4(f-8) | | 2+7x=x+38 | | 4(1+6x)=4-x | | (7x+6)+(5x+3)=(3x-9) | | 3(8)+4=y |